Forest tenure rights and REDD+: From inertia to policy solutions - Sunderlin, William D.; Larson, A.M.; Cronkleton, P. (Center for International Forestry Research, 2009)
In many developing countries, tenure in forests is not clear and subject to dispute. This will place limits on the effectiveness, efficiency and equity (3Es) of REDD+. In spite of the attention paid to the problem of insecure tenure to date, there has been little progress toward clarifying tenure arrangements. National governments need to take proactive steps to clarify tenure.